Refining clinical approaches to localized renal cell carcinoma in pregnant patients: balancing challenges and innovations - Demianiuk, M. S.; Демянюк, Марина Сергіївна (My University, 2024)
Renal cell carcinoma (RCC) during pregnancy is a rare but critical medical challenge, occurring in approximately 1 in 1,000 pregnancies [1, p. 9423]. This condition poses unique clinical and ethical dilemmas, requiring a careful balance between maternal health and fetal safety. Effective management demands a multidisciplinary, patient-centered approach that addresses the physical, psychological, and ethical complexities these patients face.
Удосконалення клінічних підходів до лікування локалізованого раку нирки у вагітних: балансування викликів та інновацій